1998
DOI: 10.1103/physrevd.57.1642
|View full text |Cite
|
Sign up to set email alerts
|

Padé-Z2estimator of determinants

Abstract: We introduce the Padé-Z 2 (PZ) stochastic estimator for calculating determinants and determinant ratios. The estimator is applied to the calculation of fermion determinants from the two ends of the Hybrid Monte Carlo trajectories with pseudofermions. Our results on the 8 3 × 12 lattice with Wilson action show that the statistical errors from the stochastic estimator can be reduced by more than an order of magnitude by employing an unbiased variational subtraction scheme which utilizes the off-diagonal matrices… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
154
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 31 publications
0
154
1
Order By: Relevance
“…For disconnected loop calculation A will be replaced by the inverse fermion matrix M −1 . Previously it was shown that the above variance for M −1 can be reduced substantially [8,2,3,5] by using a set of traceless matrices obtained from the hoping parameter expansion of the fermion matrix M as…”
Section: Noise Methods and Unbiased Subtractionmentioning
confidence: 99%
See 3 more Smart Citations
“…For disconnected loop calculation A will be replaced by the inverse fermion matrix M −1 . Previously it was shown that the above variance for M −1 can be reduced substantially [8,2,3,5] by using a set of traceless matrices obtained from the hoping parameter expansion of the fermion matrix M as…”
Section: Noise Methods and Unbiased Subtractionmentioning
confidence: 99%
“…It has been demonstrated that Z 2 noise [6] is the optimal noise with minimum variance [7]. For a given L number of Z 2 noises, variance of this estimation is given by [6,7,8] …”
Section: Noise Methods and Unbiased Subtractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leading terms in the HPE approximate the neardiagonal behavior of the operators, and the variance in the stochastic estimate of Tr O is equal to the sum of all off-diagonal elements of O. By subtracting an approximation of these terms from the estimator the variance can be reduced [11]. The exact traces of these operators can be calculated analytically since they consist of finite numbers of hops [7]; we have computed them up to 7 th order in κ.…”
Section: Hopping Parameter Improvementmentioning
confidence: 99%